Toxoplasmosis in cattle - dos Reis, Dulce Helena Camila; Maia, Maerle Oliveira; Kefler, Juliana Ribeiro Sena; da Costa, Alvimar José; Bresciani, Katia Denise Saraiva [UNESP]; Saturnino, Klaus Casaro; dos Santos, Thaís Rabelo (My University, 2014)
Bovines acquire Toxoplasma gondii mainly by congenital route and by ingestion of food or water containing oocysts, and soil contaminated with cat manure. These animals may be relatively resistant to infection, since the detection of cysts in their musculature is less frequent than in other species, despite being evidenced high occurrence of the parasite in serological surveys. In bovine the main means of prevention is the correct storage of food and water without contact with the feces of cats. Humans are infected mainly by eating raw or undercooked bovine meat as well by ingestion of not pasteurized or boiled milk. Prophylaxis for a human being is to avoid the consumption of raw animal foods must be processed by baking, boiling or freezing, and the parasite is responsive to three if performed appropriately. In this context, new worldwide perspectives referring to means of transmission, clinical signs, diagnosis and treatments in cattle will be discussed.